O17.5 Positive attitudes toward undergoing voluntary male medical circumcision among a malawian cohort. (8th July 2017) - Norris, Alison; Fokong, Kunuwo; Chemey, Elly; Garver, Sarah; Turner, Abigail Norris
Abstract : Introduction: Voluntary male medical circumcision (VMMC) is a safe, one-time intervention that provides up to 60% protection against HIV acquisition. Although this protection has led men in some communities to queue up for VMMC, in other places, including Malawi, demand remains low. Men report not undergoing VMMC fearing reduced sexual pleasure or performance, infections, bleeding, cosmetic unacceptability, and pain. VMMC can be a transformative intervention in high-HIV prevalence regions, if men decide to be circumcised. We assessed VMMC decision making during a longitudinal community-based cohort study of men and women in rural Malawi. Methods: Through our Umoyo wa Thanzi (UTHA, Health for Life ) research program in rural Lilongwe District, we interviewed reproductive-age women (n=308) and their male partners (n=140) using a standardised instrument. We assessed knowledge about VMMC for HIV risk reduction, and, drawing from the Theory of Planned Behaviour, we assessed attitudes toward VMMC, subjective norms about VMMC, and perceived behavioural control over VMMC. Results: Most participants (77%) had heard about VMMC. More men (93%) than women (70%) had heard about VMMC, and more men (87%) than women (54%) knew about VMMC for HIV risk reduction. Only 6% of men reported being circumcised. Willingness to learn about VMMC was high (82%), with few participants expressing any concerns. Among male participants, a majority (70%) reported being willing to undergo VMMC. The main concern about undergoing VMMC was that it might hurt (16%). We found high willingness (69%) to undergo VMMC if it were recommended by a health care provider. Most men (71%) expressed confidence about being able to go to a health clinic for VMMC. Conclusion: While earlier VMMC interventions were not successful in Malawi, our findings indicate that in some communities, many rural men have positive attitudes toward VMMC, would learn about and accept health care provider advice to undertake VMMC, and believe they are able to seek VMMC. VMMC should be considered a viable HIV prevention strategy in rural Malawi.